2019
DOI: 10.1002/ajh.25435
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study of carfilzomib and dexamethasone therapy for newly diagnosed multiple myeloma

Abstract: Carfilzomib and dexamethasone (Kd) has significant activity in relapsed and refractory multiple myeloma. Kd has not previously been evaluated in newly diagnosed multiple myeloma (NDMM). We report a single-arm phase 2 study of 72 patients with NDMM to evaluate the efficacy and tolerability of Kd induction.Carfilzomib was administered in two dosing cohorts with dosing of 20/45 mg/m 2 in the first 25 patients and 20/56 mg/m 2 in the subsequent 47 patients. Carfilzomib was administered on days 1, 2, 8, 9, 15 and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…In this single-arm phase II trial reported by Forsberg et al, 2019, 37 72 NDMM patients (high-risk cytogenetics, n=9 (27%)) with a median age of 59 years were given CFZ-dexamethasone (Cd) induction. CFZ delivered in two dosing cohorts, Cd1 20/45 mg/m 2 (n=25) and Cd2 20/56 mg/m 2 (n=47).…”
Section: Resultsmentioning
confidence: 99%
“…In this single-arm phase II trial reported by Forsberg et al, 2019, 37 72 NDMM patients (high-risk cytogenetics, n=9 (27%)) with a median age of 59 years were given CFZ-dexamethasone (Cd) induction. CFZ delivered in two dosing cohorts, Cd1 20/45 mg/m 2 (n=25) and Cd2 20/56 mg/m 2 (n=47).…”
Section: Resultsmentioning
confidence: 99%
“…Clinically, carfilzomib was administered on days 1, 2, 8, 9, 15, and 16 of a 28-day cycle for MM patients. 77 Here, a similar treatment scheme was adopted for CFZ-CD, CFZ-PMs, or CFZ-A6-PMs (3 mg CFZ equiv/kg) in treating LP-1 MM-bearing nude mice. The tumor growth, survival time, and body change of mice were recorded and analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…A report with in depth focus on results from the Kd induction phase of this study has been previously published. 6 2 | METHODS…”
Section: Introductionmentioning
confidence: 99%
“…Additional objectives of the study were to determine overall response rate, progression‐free survival, and regimen tolerability. A report with in depth focus on results from the Kd induction phase of this study has been previously published 6 …”
Section: Introductionmentioning
confidence: 99%